Description of Abursanema iranicum n. gen., n. sp. (Nematoda: Hexatylina, Sphaerularioidea) from Iran and its phylogenetic relationships - Yaghoubi, Ali; Pourjam, Ebrahim; Pedram, Majid; Siddiqi, Mohammad Rafiq; Atighi, Mohammad Reza (Zootaxa, 2014)
Abursanema iranicum n. gen., n. sp. is described and illustrated based on morphological, morphometric and molecular characters. The new genus is characterized by its smooth outer and annulated inner cuticle, having two incisures in lateral field, lacking stylet knobs, having pyriform terminal bulb with stem-like extension projecting into the intestine and lacking of bursa in male. The new genus belongs to the family Paurodontidae. It most closely resembles the genera Paurodontoides and Paurodontus, but has affinities based on male characters with Gymnotylenchus of the family Neotylenchidae too. From Paurodontoides, it differs by the absence of stylet knobs and having six sectors in the head framework. Compared to Paurodontus, the new genus differs by the absence of stylet knobs, structure of the pharynx and absence of a bursa in male. It differs from Gymnotylenchus mainly by lacking of stylet knobs, presence of a basal pharyngeal bulb with an extension into the intestine and in the structure of the spicules. Molecular phylogenetic studies of the new genus using 706 bp partial sequences of the 28S rDNA D2/D3 segment revealed it forming a clade with two species of Sphaerularia in both Bayesian Inference (BI) and maximum likelihood (ML) analyses with 1.00 Bayesian posterior probability (BPP) and 0.96 bootstrap support values (BS). Using 942 bp partial sequences of 18S ribosomal RNA gene, the new genus formed a clade with a species of Deladenus with 0.86 BPP and 0.62 BS in BI and ML methods, respectively. With both BI and ML methods, this clade forms a larger highly supported clade with two species of Sphaerularia.